Pembekalan dan Penguatan Karakter Bela Negara kepada Pelajar Sekolah Menengah DKI Jakarta - Nur Inayah Yushar; Marina Rospitasari; Hairunnisa Br. Sagala; Abdullah Arif (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Senior high school students represent a strategic age group transitioning into adulthood and are expected to become future leaders of the nation. In the context of achieving Indonesia’s Vision 2045, threats to national resilience are no longer dominated by military aggression, but rather by non-military challenges in the form of cognitive warfare. One prominent manifestation of this threat is the massive exposure of students to low-value digital content, commonly referred to as brain rot, on social media platforms. Such content has the potential to reduce attention span, critical thinking ability, and national awareness among adolescents. Consequently, senior high school students have become a vulnerable group in the spread of misinformation, disinformation, and ideologies that contradict Pancasila values. This community service activity aims to provide training and strengthen national defense character (bela negara) among senior high school students in Jakarta through an educational and participatory approach. The methods employed include the delivery of conceptual materials on national defense awareness and digital literacy, as well as national defense debate simulations designed to enhance students’ critical, argumentative, and ethical thinking skills. The results indicate an improvement in participants’ understanding of national defense values and their ability to express logical and responsible arguments. This activity is expected to contribute to the development of a resilient, critical, and nationally-minded young generation capable of facing contemporary challenges in the digital era.